Industrial attachment with United Engineers(s) Pte Ltd at Fusionpolis & One North MRT station project - Sulaiman Wassi. (2008)
This report describes the experience and knowledge gained through an industrial attachment in a construction company, Greatearth-United Engineers Joint Venture, working towards the completion of Fusionpolis and One North MRT station project.